Complete gravimetry of urban solid waste in the city of Manaus – AM - Rodrigues, Melquizedec Arcos; Ismail, Kamal Abdel Radi; Lino, Fátima Aparecida de Morais; de Azevedo, Inácia Oliveira (Seven Editora, 2024)
82 million tons of municipal solid waste (MSW) are generated per year in Brazil, which are destined for landfills and dumps. In the city of Manaus alone, one million tons of garbage are generated per year, which results in many public health problems, soil and river pollution, emission of gases into the air, etc. Factors such as progressive population increase combined with consumption and waste behavior, lack of awareness, low percentage of other possible treatments, such as recycling and composting have contributed to this. This work aims to describe the activities developed to characterize urban solid waste destined to the landfill of the city of Manaus-AM through gravimetric analysis, composed of three steps, required by NBR 10.007/2004: quartering, identification and weighing of waste categories. It was also possible to determine the apparent specific weight of these residuals. The studies were carried out in eighteen neighborhoods, between the years 2022 and 2023. With these data, it was found a large amount of material with the capacity to be recycled (60% + 2% on dry days and 50.0% + 1.6% on rainy days) and an average apparent specific weight of 74 Kg/m³. Thus, it is concluded that selective collection and sorting are of paramount importance, as alternatives for the reduction of waste destined to the city's landfill, enabling its useful life and the reuse of recyclable materials, bringing economic, social and environmental benefits to the city and its inhabitants. DOI:https://doi.org/10.56238/sevened2024.026-030